Identification, Structural and Phylogenetic Analysis of Lignin Biosynthesis Pathway 4CL Gene in Timber Species:Cedrus deodara Roxb. (G.Don) - Goel, Neha; Ginwal, H. S. (Indian Forester, 2019)
Lignification process allows plants flexibility to deal with various environmental stresses, and conferring on them a striking ability to remain viable even when human interventions altered lignin biosynthetic-pathway genes. The 4-coumurate ligase catalyzes the synthesis of lignin precursors as important phenylpropanoid. 4CL protein is responsible for high lignin content but severe suppression affects carbohydrate metabolism which makes deodar wood useful for timber industry. In this research evolutionary analysis, tertiary structure prediction followed by the validation for emphasizing the annotation of 4-coumurate ligase protein (4CL). The model structure showed the suitability with a member of family AMP binding enzymes and catalyzes the hydroxycinnamate - CoA thioesters as the lignin precursor from Populus tomentosa. As the future perspective molecular docking, genome wide prediction can be study for the response in defence mechanism against the pathogens and it shall be more beneficiary among the defence pathway of deodar.